(untitled) (European Journal of Interdisciplinary Research and Development, 2025)
This research examines the social relations arising from the submission of an application by a right holder or applicant to the Ministry of Justice of the Republic of Uzbekistan for the recognition of a trademark or service mark as well-known within the territory of the Republic of Uzbekistan. The subject of the study encompasses the norms of existing civil legislation, subordinate regulatory acts governing the specifics of recognizing a trademark or designation as well-known, scholarly works, and materials from law enforcement practice. Through analysis of law enforcement practice, novel criteria, not explicitly codified by the legislator, have been identified: the longevity of business operations in the market; the promotion of the trademark or designation through the most popular and accessible communication channels; a common source of origin for the goods; a defined market share; and the conferral of specific awards.